SIMULTANEOUS DETERMINATION OF FLAVONOIDS AND TRITERPENOIDS IN CYCLOCARYA PALIURUS LEAVES USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - shang, xulan; Wu, Zheng-Feng; Yin, Zhi-Qi; Zhang, Jian; Liu, Zhi-Jun; Fang, Sheng-Zuo (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Cyclocarya paliurus is an endangered plant endemic to China. The leaves of C. paliurus have been used in drug formulations and as ingredients in functional foods in China. The aim of this study was to develop an effective method to extract most of compounds and to extablish a simplified HPLC analytical method to determine the contents of major bioactive compounds simultaneously. Materials and methods: High-performance liquid chromatography (HPLC) coupled with a photodiode array detector (PDA) was used for the simultaneous determination of the major flavonoids and triterpenoids in C. paliurus leaves. Results: Ultrasonic extraction in 100% methanol for 30 min was adopted as the optimal extraction method for C. paliurus leaves. The separation conditions were optimized using a Phenomenex C18 ODS column (250 mm × 4.6 mm, 5 µm) with a mobile phase of acetonitrile and 0.02% formic acid and a detection wavelength of 205 nm. The validation data indicated that this new HPLC analytical method successfully quantified the provenance and seasonal variations of seven major compounds (three flavonoids and four triterpenoids) in C. paliurus leaves. Conclusions: This study provides a novel and simplified approach to simultaneously determine the contents of major flavonoids and triterpenoids in C. paliurus leaves. Meanwhile, the results could promote the optimization of silvicultural systems for quality control of C. paliurus.